Relationship between perceived stress and levels of blood pressure: single center study - Milena Guslov; Marko Filipović; Danijela Tasić; Sladjana Božović Ogarević; Biljana Despotović; Zorana Bogićević; Milan Arsić; Svetislav Pelemiš; Maša Petrović; Zlatko Maksimović; Nebojša Tasić (Биомедицинска истраживања, 2024)
Introduction: High blood pressure (HBP) is a significant cardiovascular risk factor, with hypertension recognized as a leading cause of global mortality. This study aims to investigate the correlation between perceived stress and blood pressure levels among patients diagnosed with hypertension. Methods: A cross-sectional study was conducted involving 80 hypertensive patients at the Institute for Cardiovascular Diseases "Dedinje". Comprehensive clinical examinations, including 24-hour ambulatory blood pressure monitoring (ABPM) and Perceived Stress Scale (PSS) assessments were performed. Results: The results revealed a significant positive correlation between PSS scores and blood pressure levels (r = 0.65, p < 0.001), indicating that higher perceived stress is associated with elevated blood pressure. Furthermore, no statistically significant difference was found between stress levels and sex or smoking status. Conclusion: These findings underscore the importance of stress management interventions in hypertension treatment, suggesting that addressing perceived stress could enhance therapeutic outcomes for patients.
Keywords: high blood pressure; perceived stress; ambulatory blood pressure monitoring; cardiovascular health